Counting work and workers in Africa: introduction to the special issue - Cissé, Chikouna; Lacroix, Annick; Mollard, Baptiste; Piguet, Laure; Renard, Léa (International labor and working class history, 2025)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS014754792510015X/resource/name/firstPage-pdf-S014754792510015Xa.jpg